Sports School Training Management: Correlation between Body Mass Index and The Physical Condition of Karate Athletes - Salsabilah, Salsabilah; Muhammad Prawibowo (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
This study aims to analyze the effect of Body Mass Index (BMI) on the physical condition of karate athletes at the Riau Province Special Sports School. The physical conditions measured include arm and abdominal muscle strength, endurance, agility, flexibility, and leg muscle power. The research method used a quantitative approach with a correlational design. The sample consisted of 9 active karate athletes (5 female and 4 male) selected through purposive sampling. Data were collected through BMI measurements and a series of physical fitness tests such as push-ups, sit-ups, beep tests, Illinois Agility Runs, sit and reach tests, and standing board jumps. Descriptive analysis results showed that 89% of athletes had a normal BMI, while 11% were underweight, with no overweight or obese athletes. There was a significant relationship between BMI and flexibility (p=0.032; r=0.711), indicating that athletes with normal BMI had better flexibility than underweight athletes. Agility showed a positive but insignificant relationship with BMI (p=0.429; r=0.303). Endurance, arm and abdominal muscle strength, and leg muscle power did not show a significant relationship with BMI. In conclusion, BMI is an important indicator in supporting athletes' flexibility, but it does not directly affect other aspects of physical fitness. Monitoring BMI and holistic training programs are recommended for optimizing karate athletes' performance.